Cosmos bipinnatus 'Sonata White' Sonata White Mexican Aster: FPS149/FP149, 6/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of the sensation-type cosmos, specifically the Cosmos bipinnatus ‘Sonata White’. It details the plant’s characteristics, including its height, spread, and flower colors. The document also covers the plant’s growth requirements, such as full sun exposure and soil preferences, and discusses its moderate drought tolerance and pest resistance. Additionally, it highlights the plant’s uses in landscaping and its propagation methods, primarily through seeds. The document concludes with information on potential pests and diseases that may affect the plant. Original publication date October 1999.